Efficacy of variable dosage of aspirin in combating methotrexate-induced intestinal toxicity. Issue 13 (14th February 2015) - Gupta, Sukesh K.; Gautam, Swetlana; Rawat, Jitendra K.; Singh, Manjari; Saraf, Shubhini A.; Kaithwas, Gaurav
<x xml:space="preserve">Abstract</x> The aim of the present study was to study in detail the effect of variable doses of aspirin on intestinal toxicity.